2019
DOI: 10.1101/589176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral graph theory of brain oscillations

Abstract: The relationship between the brain's structural wiring and the functional patterns of neural activity is of fundamental interest in computational neuroscience. We examine a hierarchical, linear graph spectral model of brain activity at mesoscopic and macroscopic scales. The model formulation yields an elegant closed-form solution for the structurefunction problem, specified by the graph spectrum of the structural connectome's Laplacian, with simple, universal rules of dynamics specified by a minimal set of glo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…The link between structural and functional connectivity is made by dynamical models, which suggest that space and time are linked via the oscillatory frequencies of certain brain networks (Atasoy et al, 2018). Further evidence for a link between spatial patterns and oscillations comes from applications of harmonic modes of the structural connectivity to faster timescales (i.e., M/EEG) (Glomb et al, 2020;Tokariev et al, 2019;Raj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The link between structural and functional connectivity is made by dynamical models, which suggest that space and time are linked via the oscillatory frequencies of certain brain networks (Atasoy et al, 2018). Further evidence for a link between spatial patterns and oscillations comes from applications of harmonic modes of the structural connectivity to faster timescales (i.e., M/EEG) (Glomb et al, 2020;Tokariev et al, 2019;Raj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this dataset, MEG, anatomical MRI, and diffusion MRI was collected for 36 healthy adult subjects (23 males, 13 females; 26 left-handed, 10 right-handed; mean age 21.75 years, age range 7-51 years). Data collection procedure has already been described previously [28]. All study procedures were approved by the institutional review board at the University of California at San Francisco and are in accordance with the ethics standards of the Helsinki Declaration of 1975 as revised in 2008.…”
Section: Model Parameter Estimationmentioning
confidence: 99%
“…Indeed, it has been suggested that brain-wide neural activity can be independent of microscopic local activity of individual neurons [21,22,17,6,23,13], and instead may be regulated by long-range structural connectivity [24][25][26][27]. Based on this hypothesis, Raj and colleagues had earlier developed a hierarchical, linear, analytic spectral graph theory model (SGM) which could accurately capture empirical MEG spectra and spatial distribution of alpha and beta frequency bands [28].…”
Section: Introductionmentioning
confidence: 99%
“…A modeling approach lying between these two extremities was only recently demonstrated by a linear biophysical model called the spectral graph theory model (SGM) that can accurately capture the wide-band static frequency spectra obtained from MEG. This model incorporates biophysics while maintaining parsimony and requiring minimal computation speed [35].…”
Section: Introductionmentioning
confidence: 99%